2022
DOI: 10.1128/jcm.02229-21
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Atypical Shiga Toxin Gene Sequences and Description of Stx2j, a New Subtype

Abstract: Shiga toxin (Stx) is the definitive virulence factor of Shiga toxin-producing Escherichia coli (STEC). Stx variants are currently organised into a taxonomic system of three Stx1 (a,c,d) and seven Stx2 (a,b,c,d,e,f,g) subtypes. In this study, seven STEC isolates from food and clinical samples possessing stx2 sequences that do not fit current Shiga toxin taxonomy were identified. Genome assemblies of the STEC strains was created from Oxford Nanopore and Illumina se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Although Stx2k-STEC has only been reported in China so far, it is not unlikely that Stx2k-STEC may occur in other countries but has not been identified or has been assigned as another Stx2 subtype; for instance, Stx2k was initially assigned as a new Stx2e variant ( 20 ). One example is that the recently designated Stx2h subtype was previously only detected in isolates from Tibetan marmots ( 9 ) but has been reported recently from sprouts in Canada ( 11 ). The host ranges and specificities of different stx subtypes need further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Stx2k-STEC has only been reported in China so far, it is not unlikely that Stx2k-STEC may occur in other countries but has not been identified or has been assigned as another Stx2 subtype; for instance, Stx2k was initially assigned as a new Stx2e variant ( 20 ). One example is that the recently designated Stx2h subtype was previously only detected in isolates from Tibetan marmots ( 9 ) but has been reported recently from sprouts in Canada ( 11 ). The host ranges and specificities of different stx subtypes need further study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new Stx2 subtypes have been identified: Stx2h to Stx2m and Stx2o ( 8 13 ). Of these, Stx2j, Stx2k, Stx2m, and Stx2o subtypes have been identified in clinical isolates ( 11 , 13 ), suggesting clinical relevance of new Stx subtypes. Interestingly, Stx2k-STEC strains have been identified in E. coli strains from a variety of hosts and sources, including diarrheal patients, animals (goats, sheep, and pigs), and raw meat (mutton and beef), in China over time ( 12 , 14 ), while they not yet been reported in any other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the EcOH database ( https://github.com/katholt/srst2/blob/master/data/EcOH.fasta ), VFDB database ( http://www.mgc.ac.cn/VFs/main.htm ), and Comprehensive Antibiotic Resistance Database (CARD) ( https://card.mcmaster.ca ), were used to determine the serotypes, virulence genes and antimicrobial resistance genes, respectively, using ABRicate version 1.0.1 ( https://github.com/tseemann/abricate ) with default parameters. For stx subtyping, an in-house stx subtyping database was created with ABRicate by integrating representative nucleotide sequences of all identified stx1 and stx2 subtypes, consisting of stx1 / stx2 subtypes previously reported by Scheutz et al (2012) , and several recently-reported Stx2 subtypes, Stx2h-Stx2m and Stx2o ( Bai et al, 2021 ; Gill et al, 2022 ). The assemblies were then compared against the in-house stx subtyping database using ABRicate version 1.0.1.…”
Section: Methodsmentioning
confidence: 99%
“…5 The defining genetic feature of STEC is the integration of one or more lamdoid bacteriophage encoding Shiga toxin genes, of which there are two types (stx1 and stx2) and multiple subtypes (stx1a-c, stx2a-k). 6 There is a clear association between Shiga toxin profile and clinical severity, with strains harbouring stx2a substantially more likely to cause severe disease (including haemolytic uraemic syndrome) than other strains. 7,8 Additionally, strains encoding stx1a are associated with patients presenting with bloody diarrhoea.…”
Section: Introductionmentioning
confidence: 99%